Acidente de Transporte Terrestre em Bauru SP : características da morbimortalidade em 2004 - Dias, Maria Amélia Costa (2007)
Traffic accidents are one of the biggest Public Health problems in Brazil. It is also one of the most important categories in the External Causes group, affecting the morbimortality of the population due to the precocity of the occurrences, in most cases. Moreover, costs are very high: hospitalization, medical care, disability (temporary or permanent), among others. This study aimed to describe morbimortality from traffic accidents in the city of Bauru, SP, in the year 2004. The data used in this research were collected from SIM (Mortality Information System); SIH (Hospital Information System); IBGE (Brazilian Institute of Geography and Statistics); and Bauru s Traffic Community Base São Paulo Police Department. The study shows that mortality rate from traffic accidents is 13,89 per 100 thousand inhabitants, being male mortality rate higher, decreasing with age, in a population age 20 to 29. Traffic was the third cause of death in the city. The category with a higher risk of hospitalization was the grouping of external causes V01 to V09 traumatized pedestrian in traffic accident (97,65%); higher in male victims, age 30 to 39. Hospitalization from traffic accidents adds up to 383 cases, which corresponded to a total of 13,30% and was the trird cause of hospitalization, affecting the population age 30 to 39. An important sub-record of traffic accidents from the Police Department database statistics has been observed. It varied according to the total of deaths and to the number of accidents and victims. It has been concluded that being aware of the magnitude of these aspects is fundamental for specific prevention strategy and for morbimortality reduction. It is also fundamental to generate and publish more precise data so that the society is aware of this kind of reality.